Exploring the Role of Professional Learning Community on Teacher’s Instructional Fits: A Voice of Indonesian Teachers - Bachtiar Bachtiar; Sri Dewi Nirmala (Journal of Innovation in Educational and Cultural Research, 2023)
In the aftermath of the COVID-19 pandemic, technological resources and their utility in education have undergone a revolution, especially in the Indonesian education system. There is an urgent need to develop strategies for maximizing the use of advancing technological tools to improve students' academic achievement. This research aims to investigate the challenges that teachers face in employing blended learning and the benefits they get from their involvement in Professional Learning Communities (PLCs). The current study employed Mixed Method Research involving 30 respondents to fill out the questionnaire, and six were invited to be interviewed. The results demonstrate that teachers' participation in PLCs has enabled them to enhance their pedagogical competence and technology literacy. The results also show that teachers have applied blended learning as an emerging learning approach in post-Covid-19. The study results imply that teachers' involvement in PLC learning activities affects their competence to integrate technology into their teaching practice, including implementing blended learning. The study results contribute to the dissemination of information to educational stakeholders and academic forums for teachers as input for undertaking effective professional development for teachers and as references for future research.